Pengaruh corporate social responsibility, capital expenditure, keputusan investasi dan leverage terhadap nilai perusahaan pada perusahaan sektor consumer goods yang terdaftar di Bursa Efek Indonesia tahun 2016-2019 - Namira Ufrida Rahmi; Vandystio Danantho (Owner : Riset dan Jurnal Akuntansi, 2022)
The purpose of this study was to examine the effect of Corporate Social Responsibility, Capital Expenditure, Investment Decisions, and Leverage on Firm Value in consumer goods industry sector companies listed on the Indonesia Stock Exchange n 2016-2019 period. Firm value show how effective is the firm performance in line with the prosperity of shareholders and perception of investors to the company. This research used a method with a quantitative descriptive approach. The population in this study were the consumer goods companies listed in Indonesia Stock Exchange (IDX) during the period 2016 to 2019 with a total of 40 companies and the sampling technique used purposive sampling and obtained 24 companies in consumer goods sector. Data analysis used multiple linear regression analysis, classical assumption test, the coefficient of determination test, F test and t test. The results of the study show that partially corporate social responsibility, capital expenditure and investment decisions have significant effect on the firm value but leverage have no effect on the firm value. Variable corporate social responsibility, capital expenditure, investment decisions and leverage simultaneously have a significant effect on firm value in consumer goods industry sector listed on Indonesia Stock Exchange in 2016-2019.